Divergent Roles of Inflammation in Skeletal Muscle Recovery From Injury - Howard, Emily E.; Pasiakos, Stefan M.; Blesso, Christopher N.; Fussell, Maya A.; Rodriguez, Nancy R. (Frontiers in Physiology, 2020)
A transient increase in local pro-inflammatory cytokine expression following skeletal muscle injury mediates the repair and regeneration of damaged myofibers through myogenesis. Regenerative capacity is diminished and muscle wasting occurs, however, when intramuscular inflammatory signaling is exceedingly high or persists chronically. An excessive and persistent inflammatory response to muscle injury may therefore impair recovery by limiting the repair of damaged tissue and triggering muscle atrophy. The concentration-dependent activation of different downstream signaling pathways by several pro-inflammatory cytokines in cell and animal models support these opposing roles of post-injury inflammation. Understanding these molecular pathways is essential in developing therapeutic strategies to attenuate excessive inflammation and accelerate functional recovery and muscle mass accretion following muscle damage. This is especially relevant given the observation that basal levels of intramuscular inflammation and the inflammatory response to muscle damage are not uniform across all populations, suggesting certain individuals may be more susceptible to an excessive inflammatory response to injury that limits recovery. This narrative review explores the opposing roles of intramuscular inflammation in muscle regeneration and muscle protein turnover. Factors contributing to an exceedingly high inflammatory response to damage and age-related impairments in regenerative capacity are also considered.